Synthetic Layered and Tube-Like Silica Nanoparticles as Novel Supports for Metallocene Catalysts in Ethylene Polymerization - Zapata-Ramirez, P (Elsevier B.V., 2011)
Synthetic hybrid layered (HLNP) and tube-like (SNTP) silica nanoparticles were used to support the (nBuCp)2ZrCl2 metallocene catalyst for ethylene polymerization. Different amounts of zirconium were directly supported on the nanoparticles either with or without methylaluminoxane (MAO) treatment, allowing the effect of catalyst loading and particle surface on catalytic behaviour and polymer properties to be studied. Our results show that outstanding catalytic activities, comparable to a homogeneous polymerization, can be obtained when the metallocene catalyst is directly supported on the silica nanoparticles. The catalytic activity of the metallocene catalyst supported on MAO-treated nanoparticles increases with the amount of zirconium in the support. The molecular weights of the polyethylenes synthesized using both supported systems were higher than those from homogeneous polymerization. TEM images show that both nanoparticles were well dispersed in the polymer matrix and the HLNPs were exfoliated into the polymer. The presence of these nanoparticles in the resulting polymer improves the thermal stability of the matrix. © 2011 Elsevier B.V. All rights reserved.